2002
DOI: 10.1037/0022-0167.49.3.342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Asian American client adherence to Asian cultural values, session goal, and counselor emphasis of client expression on career counseling process.

Abstract: Seventy-eight Asian American college students who were experiencing career uncertainty engaged in a counseling session with a European American female counselor who focused on either immediate resolution of the problem or insight attainment through exploration of the problem and who emphasized client expression of either cognition or emotion. Clients with high adherence to Asian cultural values perceived increased counselor empathic understanding and stronger client-counselor working alliance than did clients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
84
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 30 publications
9
84
2
Order By: Relevance
“…Psychotherapists' MCO Psychotherapy studies have found that clients' perceptions of their psychotherapists' MCO are positively associated with clients' ratings of working alliance, session quality, psychotherapists' empathy, and general competence (Constantine, 2002(Constantine, , 2007Fuertes & Brobst, 2002;Fuertes et al, 2006;Kim et al, 2002;Li & Kim, 2004). The primary criterion variable in several studies has been clients' satisfaction with services, which has also been positively related to clients' perceptions of their psychotherapists' MCO (Constantine, 2002(Constantine, , 2007Fuertes & Brobst, 2002;Fuertes et al, 2006).…”
Section: Previous Studies On Clients' Perceptions Of Theirmentioning
confidence: 99%
“…Psychotherapists' MCO Psychotherapy studies have found that clients' perceptions of their psychotherapists' MCO are positively associated with clients' ratings of working alliance, session quality, psychotherapists' empathy, and general competence (Constantine, 2002(Constantine, , 2007Fuertes & Brobst, 2002;Fuertes et al, 2006;Kim et al, 2002;Li & Kim, 2004). The primary criterion variable in several studies has been clients' satisfaction with services, which has also been positively related to clients' perceptions of their psychotherapists' MCO (Constantine, 2002(Constantine, , 2007Fuertes & Brobst, 2002;Fuertes et al, 2006).…”
Section: Previous Studies On Clients' Perceptions Of Theirmentioning
confidence: 99%
“…In contrast, when the counselors were European American, the clients with low AVS scores rated the counselors as more empathic than did the clients with high AVS scores. However, in another study of single-session counseling, Kim, Li, and Liang (2002), using all European American counselors, found that Asian American clients with high scores on the AVS perceived greater counselor empathy and working alliances than did clients with low AVS scores. This latter finding is directly contradictory to the findings from Kim and Atkinson's (2002) sample with European American counselors.…”
mentioning
confidence: 99%
“…A range of variables has been investigated, including counselling style (Atkinson & Matsushita, 1991), session goals (Kim, Li, & Liang, 2002), counsellor emphasis on client expression (Kim et al, 2002), and counsellor self-disclosure (Kim, Hill, Gelso, Goates, Asay, & Harbin, 2003). For example, Kim et al (2002) examined clients' reactions to two types of session goals: in one condition European American counsellors focused on immediate resolution of clients' problems, and in the other the attainment of insight through exploration. At the end of the session, clients in the "immediate resolution" condition perceived a stronger working alliance with the counsellor.…”
mentioning
confidence: 99%